Can AI Improve Healthcare Quality Measurement? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2024)
In an era of rapid technological advancement, the healthcare sector is increasingly turning to artificial intelligence (AI) to address some of its most press...
Keywords: AI in Medical Education and Future of Healthcare; Improve; Healthcare; Quality; Artificial Intelligence; Machine Learning; Medical Imaging